HAK ASASI MANUSIA DALAM KEBEBASAN BERPENDAPAT BERKAITAN DENGAN MAKAR - Paidjo, Paidjo; Hufron, Hufron; Herlin Setyorini, Erny (Yayasan Akrab Pekanbaru, 2019)
The study aims to find out and analyse what qualifications for criminal acts of Macar and to know and analyze when the perpetrators of the matter convey public opinion can be categorized as Makar crime. The methods of study used are normative juridical, based on the principles of the law, the rules of the law and the legislation or books/literature relating to Makar action. Normative legal research is a study that examines prevailing norms including laws that have relevance to the problem as the source of legal material. Based on the results of the study can be concluded that communicating in public is permissible because it is part of human rights, namely the right of freedom to convey opinion as stipulated in article 28 CONSTITUTION of the Republic of Indonesia year 1945. Expressed opinion may be categorized as a criminal offence if it meets the provisions of article 88 of KUHAP. In article 88 the criminal CODE stated that there is an evil agreement, if two or more people have agreed to commit the crime, continued in article 88 of the bus with the overthrow of the government is negating or changing the form of unauthorized government under the Constitution. Therefore, presenting opinions in public can be categorized as Makar action if it is evident that in the implementation there is an indication or that has an intention to overthrow the government, with the intention to kill, or seize independence, or negate the ability of the President or vice President ruled.